Kontroversi Dan Komparasi Prinsip Asuransi Syariah (Takaful) Perspektif DSN- MUI, Lembaga Tarjih Muhammadiyah, Nahdatul Ulama Dan Ulama Kontemporer - Nurwahidah, Dede; Abdul Hakim, Atang (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
The development of sharia insurance in Indonesia continues to grow every year, so that the sustainability of sharia insurance has caused controversy among several Ulama circles, Islamic mass organizations such as NU and Muhammadiyah. Because many people think that sharia insurance is the same as conventional insurance. From the results of this comparison, it can be concluded that there are several groups of contemporary ulama who allow sharia insurance law based on social interests, so that in its implementation it is only permitted in tabarru' or ta'awun contracts. The aim of this research is to understand the concept of takaful which is based on sharia principles, to find out how the MUI views takaful in Indonesia. This research method uses a qualitative library research approach, in the form of literature studies sourced from secondary data, namely books, scriptures, journals and the Koran. From the discussion it is concluded that there are two controversies regarding the development of takaful, the first is allowing and the second is prohibiting. Basically, the principle of sharia insurance (takaful) can continue as long as it does not ignore or violate the provisions of sharia law that have been established by Allah SWT. One solution is to implement takaful purely with the principle of the ta'awun contract (ask for help).